Politiques éducatives et expériences scolaires des jeunes trans au Québec et en France : un panorama - Gabrielle Richard; Arnaud Alessandrin (Genre, Sexualité et Société)
According to surveys conducted in Quebec (Canada) and in France, school experiences of trans youth are particularly chaotic. Despite similar ground-based observations, France and Quebec present school environments that are in some ways different for their trans youths. In this comparative paper, we interrogate the existence of educational policies that aim at reducing and preventing transphobia in high schools, as well as promoting a safe and welcoming environment for trans students. In Quebec, despite the legitimacy conferred to the fight against homophobia since the 2000s, the schooling experiences of trans students have only barely been subjected to specific strategies. In French schools, it remains impossible to talk about trans issues, partly because of the predominance of the notion of equality between girls and boys. Only concerted efforts from political and educational instances, as well as a frank discussion about gender issues, can ultimately weaken the heteronormativity in schools in France and in Quebec.